Dynamics of Bianchi type- VI anisotropic dark energy cosmological model with massive scalar field in Lyra manifold - Ram S.; Verma M.K. (My University, 2025)
The paper deals with the study of anisotropic dark energy and massive scalar field in the evolution of spatially homogeneous Bianchi type-VI cosmological model in the framework of Lyra geometry. Exact solution of Einstein’s field equations is obtained by using two supplementary physical and mathematical conditions which correspond to an anisotropic dark energy cosmological model for all time. Some physical and dynamical behaviors of the model are discussed. The model may be physically significant for discussion on early stages of evolution of the universe. © 2021, Indian Association for the Cultivation of Science.